The Role of Internal Factors on Vehicular Mobility - Mdimi, Aziz; John, Geoffrey; Mhilu, Curthbert; Bwire, Hannibal; Kihedu, Joseph (Tanzania Journal of Engineering and Technology, 2025)
<span style="color: #333333; font-family: Montserrat, Helvetica, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Vehicle mobility internal factors are influenced by the performance state of the road surface quality, governor, engine, gear train, differential unit and mobility unit. Studies on vehicular mobility models exist for off-road external factors but absent on on-road internal factors. The on-road internal factors model describes the vehicular mobility performance as a function of internal factors. In the current undertaking, results are generated by the determination of mobility performance characteristics with the application of 2nd Order Ordinary Differential Equations and using Laplace operator with MATLAB Software simulation. The effect of road surface against the time taken varies accordingly. At a pedal force of 50 N, a higher road roughness, indicated by an International Roughness Index (IRI) of 2.8 m/km, was observed on a road segment with notable roughness. The time ensued is 96.0 seconds at a tractive force of 4500 N on pedal force of 50 N indicating a longer transacted time and low fuel displacement resulting in lower engine revolution speed. The lowest roughness at a value 2.0 m/km, time taken was 17.5 seconds to cover the distance at a tractive force of 17750 N. The results suggest that the greater road roughness (IRI) may lead to a longer time taken to cover the distance. As a consequence of high IRI a vehicle travels more slowly and impact on overall mobility. Thus, maintenance on the road surface should be done regularly to better road surface quality.